Gender and Islam through Leila Ahmed’s Lens: Methodology, Social Realities, and Personal Insights: - Hafizah, Yulia (Muadalah, 2024)
The study on women and gender in Islam has become an intriguing subject for many scholars over the past few decades. One of these is Leila Ahmed's work entitled "Women and Gender in Islam: Historical Roots in Modern Debate." This work has made a significant contribution in deconstructing stereotypes and expanding understanding of how religion and culture shape views of women in Muslim societies. This article aims to analyze Leila Ahmed's thoughts on the methodological aspects and approaches she employs. The research utilizes a qualitative literature review method with documentary analysis techniques. The research findings indicate that Leila Ahmed's life experiences, crossing social and cultural boundaries, have had a profound influence on the development of her scholarly identity. She has encountered a personally "lived" Islam, acquired and taught by her mother, as well as a ritualistic and at times oppressive Islam imposed by the state. She has experienced educational opportunities afforded to her by Western influences in Egypt, yet suffered racism and stereotypes from teachers and peers in England. These diverse experiences have imbued meaning into her work and compelled her to provide balanced and sensitive analyses in her book. There, Leila Ahmed does not highlight what is right or wrong but instead portrays a complex situation by presenting multiple possible responses to each question. Keywords: Cultural and Social Contexts; Islam and Gender; Leila Ahmed; Methodology in Islamic Studies; Women and Gender in Islam